Antimicrobial effects of TiO2 and Ag2O nanoparticles against drug-resistant bacteria and leishmania parasites. (August 2011) - Allahverdiyev, Adil M; Abamor, Emrah Sefik; Bagirova, Malahat; Rafailovich, Miriam
Nanotechnology is the creation of functional materials, devices and systems at atomic and molecular scales (1–100 nm), where properties differ significantly from those at a larger scale. The use of nanotechnology and nanomaterials in medical research is growing rapidly. Recently, nanotechnologic developments in microbiology have gained importance in the field of chemotherapy. Bacterial strains that are resistant to current antibiotics have become serious public health problems that raise the need to develop new bactericidal materials. Metal oxide nanoparticles, especially TiO2 and Ag2 O nanoparticles, have demonstrated significant antibacterial activity. Therefore, it is thought that this property of metal oxide nanoparticles could effectively be used as a novel solution strategy. In this review, we focus on the unique properties of nanoparticles, their mechanism of action as antibacterial agents and recent studies in which the effects of visible and UV-light induced TiO2 and Ag2 O nanoparticles on drug-resistant bacteria have been documented. In addition, from to previous results of our studies, antileishmanial effects of metal oxide nanoparticles are also demonstrated, indicating that metal oxide nanoparticles can also be effective against eukaryotic infectious agents. Conversely, despite their significant potential in antimicrobial applications, the toxicity of metal oxide nanoparticles restricts their use in humans. However, recent studies infer that metal oxide nanoparticles have considerable potential to be the first-choice for antibacterial and antiparasitic applications in the future, provided that researchers can bring new ideas in order to cope with their main problem of toxicity.